2014
DOI: 10.1016/j.jmb.2014.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Lysophospholipid-Containing Membranes Modulate the Fibril Formation of the Repeat Domain of a Human Functional Amyloid, Pmel17

Abstract: Pmel17 is an important protein for pigmentation in human skin and eyes. Proteolytic fragments from Pmel17 form fibrils upon which melanin is deposited in melanosomes. The repeat domain (RPT) derived from Pmel17 only forms fibrils under acidic melanosomal conditions. Here, we examined the effects of lipids on RPT aggregation to explore whether intramelanosomal vesicles can facilitate fibrillogenesis. Using transmission electron microscopy, circular dichroism, and fluorescence spectroscopy, fibril formation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 62 publications
2
46
1
Order By: Relevance
“…During melanosome maturation, the intralumenal pH increases from acidic (pH ~4) in early stages to near-neutral pH upon full maturation (11). Previous work from our lab and others have shown that the repeat (RPT) domain, constituting residues 315-444, forms amyloid fibrils in vitro under acidic conditions similar to those found in the early stages of melanosome maturation (9,10,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Exposure of pre-formed RPT fibrils to cytosolic conditions (pH ≥7) leads to rapid dissolution in vitro, which is proposed to protect against cytotoxicity in vivo should fibrils escape the melanosome (9,10,17).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…During melanosome maturation, the intralumenal pH increases from acidic (pH ~4) in early stages to near-neutral pH upon full maturation (11). Previous work from our lab and others have shown that the repeat (RPT) domain, constituting residues 315-444, forms amyloid fibrils in vitro under acidic conditions similar to those found in the early stages of melanosome maturation (9,10,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Exposure of pre-formed RPT fibrils to cytosolic conditions (pH ≥7) leads to rapid dissolution in vitro, which is proposed to protect against cytotoxicity in vivo should fibrils escape the melanosome (9,10,17).…”
Section: Introductionmentioning
confidence: 82%
“…Expression and purification of RPT − Plasmids encoding either lRPT or sRPT constructs with a Cterminal hexa-histidine tag were transformed into E. coli BL21(DE3) competent cells (Fisher Scientific) and expressed by the NHLBI Protein Expression Facility as described prior (18). Cell pellets (~10 g/purification) were then resuspended in 50 mL of lysis buffer (6 M GuHCl, 100 mM NaCl, 100 mM Na2HPO4, 20 mM imidazole, pH 7.4) and sonicated (on ice) for 60-s (50% duty cycle, output control = 5) using a 3-mm tapered microtip attached to a Branson Sonifier 450.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, in vitro the kinetics of RPT fibril formation is extremely slow (in the range of days to weeks), while in melanocytes PMEL fibrils are formed very quickly to avoid any toxicity. However, addition of lysophospholipid-containing vesicles can shorten the lag time (less than 4 h) and enhance the growth rate of RPT fibrillation [ 56 ]. These in vitro data are in line with the potential role of lipid membranes, such as ILVs, as nucleating platforms of PMEL amyloid fibrils.…”
Section: Pmel Fibrillation In Vitromentioning
confidence: 99%
“…Since melanosome membranes contain a high content of lysophospholipids (lysolipids), their effects on RPT fibril formation were studied. [55] Vesicles containing either negatively charged lysophosphatidylglycerol (LPG) or zwitterionic lysophosphatidylcholine (LPC) stimulated RPT fibril formation, with LPG exerting the greater effect by reducing the apparent lag phase during aggregation.…”
Section: Lysolipids Modulate Rpt Fibril Formationmentioning
confidence: 99%
“…In fact, the only known glycosylation sites are located in the region between residues 328–344, [36] which is located far away from the C-terminal RPT amyloid core that we have characterized. [47, 4950, 5556] Specifically, in our work, we determined by deleting residues, 405–410, where there is no glycosylation, amyloid formation is ablated. [49] In addition, the notion that a glycosylated RPT would be unable to fibrillate in vivo is questioned by the fact that a short C-terminal segment of RPT composed of 405 VSIVVLSGT 413 alone was capable of self-assembling into amyloid fibrils.…”
Section: The Dark Side Of Rptmentioning
confidence: 99%